The Construction of Truth Through Immersive Graphics in Thai Television News Programs - Udomlappaisan, Chinnagrit; Nedpogaeo, Asawin (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This qualitative research aims to analyze the construction of truth through immersive graphics in news reporting on Thai television news programs. The study collected data through in-depth interviews with 15 key informants from four television stations that use Vizrt immersive technology and software in news production. Participants included personnel responsible for news departments, program production, and graphic design. The research findings indicate that although news presentation principles emphasize objectivity, the study reveals that immersive graphics in news reporting significantly exhibit subjective characteristics. Throughout the production process, traces of ideologies, values, attitudes, conceptual frameworks, design approaches, and creative workflows reflect selection, filtering, and customization by individuals or organizations, representing the subjective reality of producers that appears implicitly in the work. Consequently, the truth conveyed through immersive graphics possesses characteristics of pragmatic truth rather than conforming to the fixed concept of objective truth.